Faktor-Faktor Yang Memperkuat dan Memperlemah Nilai Perusahaan - Akhmadi Akhmadi; Bambang Mahmudi (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to build a research model to overcome the gap that occurs in the effect of dividend policy on firm value by including profitability as a moderating variable. The population of this research is 69 companies. While the sample is determined by 20 companies in the LQ-45 index, determined by purposive sampling technique, data analysis using descriptive statistics, regression moderating analysis, classic assumption test, partial test and moderation test. The results of the study prove that dividend policy has a significant direct relationship to the value of the company. Likewise, the profitability performance of companies in the LQ45 index has a significant directional relationship. Profitability performance in companies in the LQ45 index is not a variable that can provide a strong response either to the strengthening or weakening of dividend policy and corporate value.